Grammatical Approaches to Language Processing Essays in Honor of Lyn Frazier - Carlson, Katy.; Clifton, Jr., Charles; Fodor, Janet Dean.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book contains papers that were written to honor Professor Lyn Frazier on the occasion of her retirement from the University of Massachusetts Amherst. Some were presented at the Lynschrift on May 19-20, 2018; others were written especially for this volume. The papers report original research on, or research-based theoretical analyses of, several of the domains that Professor Frazier contributed to during her career. The volume begins with a brief overview of Professor Frazier's research contributions and an appreciation of the contributions she has made to the field of psycholinguistics and to her students and colleagues. The next several chapters discuss the roles that prosody plays in language processing, and the volume continues with chapters on the topic that established Professor Frazier as a major psycholinguistic theorist, syntactic processing. The volume then explores the roles semantics and pragmatics play in language comprehension, and concludes with reports of applications and extensions of research on language processing. All chapters were contributed by current and former students and colleagues of Professor Frazier in gratitude for the impact she has had on their lives and careers.
Lyn Frazier's contributions to psycholinguistics: An appreciation; Charles Clifton, Jr., Brian Dillon, and Adrian Staub -- Center-embedded sentences: An online problem or deeper? Janet Dean Fodor, Benjamin Macaulay, Danielle Ronkos, Taletha Callahan, and Tyler Peckenpaugh -- Contrastive prosody and the subsequent mention of alternatives during discourse processing; Amy Schafer, Amber Camp, Hannah Rohde, Theres Grüter -- Alternatives on demand and locality: Resolving discourse-linked wh-phrases in sluices; Jesse A. Harris -- The division of labor between structure building and feature checking during sentence comprehension; Markus Bader -- Real-time commitments in processing individual/degree polysemy; Margaret Grant, Sonia Michniewicz, Jessica Rett -- Negative polarity items as collocations: Experimental evidence from German; Frank Richter, Janina Radό -- What eye movements can and cannot tell us about wh-movement and scrambling; Irina A. Sekerina, Anna K. Laurinavichyute, Olga V. Dragoy -- When all linguists did not go to the workshop, none of the Germans but some of the French did: The role of alternative constructions for quantifier scope; Barbara Hemforth, Lars Konieczny -- Definites, domain restriction, and discourse structure in online processing; Florian Schwarz -- Processing coercion in Brazilian Portuguese: Grinding objects and packaging substances; Suzi Lima -- Incrementality in processing complements and adjuncts: Construal revisited; Britta Stolterfoht, Holger Gauza, and Melanie Störzer -- Event knowledge and verb knowledge predict sensitivity to different aspects of semantic anomalies in aphasia; Michelle Colvin, Tessa Warren, and MichaelWalsh Dickey -- Who cares what who prefers? A study in judgment differences between syntacticians and non-syntacticians; Gisbert Fanselow, Jana Häussler, and Thomas Weskott -- How just is justice? Ask a psycholinguist; Janet Randall -- C-command in discourse: Syntactic principles beyond the sentence and their consequences foracquisition theory; Tom Roeper.
Keywords: Psycholinguistics; Language acquisition; Grammar, Comparative and general -- Syntax; Semiotics; Pragmatics; Psycholinguistics and Cognitive Lingusitics; Language Acquisition and Development; Syntax; Semiotics; Pragmatics